RuCo alloy trifunctional electrocatalysts with ratio-dependent activity for Zn–air batteries and self-powered water splitting. Issue 12 (14th January 2021) - Pei, Yu; He, Wangtao; Wang, Minmin; Wang, Jin; Sun, Tongming; Hu, Lanping; Zhu, Jinlin; Tan, Yanfeng; Wang, Jiacheng
Abstract : Herein, we reported a RuCo alloy with nitrogen-doped porous carbon (RuCo/NPC) as efficient trifunctional electrocatalysts for Zn–air batteries and water splitting. Abstract : Herein, we reported a RuCo alloy with nitrogen-doped porous carbon (RuCo/NPC) as efficient trifunctional electrocatalysts for Zn–air batteries and water splitting. The versatility and catalytic activity of this catalyst is achieved by adjusting the Ru/Co ratio. The as-assembled Zn–air battery and overall water splitting with RuCo/NPC present outstanding catalytic performances.